(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Nugroho RA, Subagyono DJN, Arung ET. 2020. Isolation and characterization of Botryococcus braunii from a freshwater environment in Tenggarong, Kutai Kartanegara, Indonesia. Biodiversitas 21: 2331-2336. The use of microalgae as an alternative source of oil has gained much attention in recent years. The present study was conducted to isolate and characterize microalgae Botryococcus braunii from a freshwater environment, located in Tenggarong, Kutai Kartanegara, East Kalimantan, Indonesia. B. braunii were cultured and determined their growth in terms of biomass yield and the presence of lipid globules by red Nile staining. Dry biomass, phosphate, and protein content of cultured B. braunii were measured at 3 days of intervals for 24 days. Biomass yield, hydrocarbon, carotenoid, and chlorophyll content were determined at the pH range of 6, 6.5, 7, 7.5, and 8 and various CO2 concentrations. The result showed that B. braunii collected from freshwater in Tenggarong can produce lipid globules. The highest growth of B. braunii was reached at day 15, while the optimal phosphate content was on the 12th day, and the protein was relatively stable during culture. The optimal weight of B. braunii biomass was reached at pH 7 and 4% CO2 and the highest hydrocarbon content was obtained at pH 8 and 4% CO2. The highest chlorophyll and carotenoid contents were obtained 4% CO2. In conclusion, B. braunii collected from Tenggarong was successfully cultured and able to produce lipid globules. The optimal conditions for its growth and production of hydrocarbon, phosphate, protein, chlorophyll, and carotenoid were at pH of 7-8 and 4% CO2.